Seismic Performance of Large Underground Water Tank Structures Considering Fluid–Structure Interaction - Fengyuan Xu; Chengshun Xu; Mohamed Hesham El Naggar; Xiuli Du (Buildings)
The widespread application of large underground water tank structures in urban areas necessitates reliable design guidelines to ensure their safety as critical infrastructure. This paper investigated the seismic response of large underground water tank structures considering fluid–structure interaction (FSI). Coupled Eulerian–Lagrangian (CEL) was employed to analyze the highly nonlinear FSI caused by intense fluid sloshing during earthquakes. The patterns of fluid sloshing amplitude observed from the finite element model were summarized based on analyses of fluid velocity, hydrodynamic stress components, and overall kinetic energy. In addition, the seismic response of the water tank structure was thoroughly assessed and compared with the simulation results of the empty tank structure. The results indicate that significant fluid sloshing occurs within the structure under seismic excitation. The amplitude of fluid sloshing increases horizontally from the center toward the edges of the structure, corresponding to higher hydrodynamic loads at the side area of the structure. By comparing the analysis results of the water tank structure with and without water, it was concluded that FSI is the primary cause of structural damage during an earthquake. The hydrodynamic loads on the roof, diversion walls, and external walls lead to significant localized damage.